Лучшие помощники
10 ноября 2022 00:00
1174

< strong>упростите выражение любая < / strong>

image
2 ответа
Посмотреть ответы
Ответ:
\dfrac
Пошаговое объяснение:
\bigg (\dfrac+4mp}-\dfrac-4mp} \bigg ) \cdot \dfrac-m^}}=\bigg (\dfrac-\dfrac \bigg ) \cdot \dfrac-m^}}=
=\dfrac{(m-4p)(m-4p)-(m+4p)(m+4p)} \cdot \dfrac-m^}}=\dfrac{(m-4p)^-(m+4p)^}-(4p)^)} \cdot
\cdot \dfrac-m^}}=\dfrac-8mp+16p^-(m^+8mp+16p^)}-16p^)} \cdot \dfrac-m^}}=
=\dfrac-m^-8mp-8mp+16p^-16p^}-16p^)} \cdot \dfrac-m^}}=\dfrac{-16mp}-16p^)} \cdot \dfrac-m^}}=
=\dfrac-m^} \cdot \dfrac-m^}}=\dfrac}=\dfrac=\dfrac;
0
·
Хороший ответ
11 ноября 2022 10:40
Пошаговое объяснение:
1.
Упростим выражение в скобках:
\frac -\frac=\frac-\frac=\frac{(m-4p)^2-(m+4p)^2} =\\\frac = \frac{-16mp}=  \frac.
2.
\frac*\frac=\frac.
0
11 ноября 2022 10:40
Остались вопросы?
Найти нужный